A study on knowledge, perception and practice (KPP) of preventive measures against respiratory tract infections, factors associated with hand hygiene practices and the effect of supplying handrub among Malaysian Hajj pilgrims 2013 - Salmuna@Ayub, Zeti Norfidiyati (2016)
Introduction: Every year, approximately 2 million pilgrims from all over the world gathered in Mecca to participate in Hajj, one of the pillar of Islam. Extreme congestion of people and heat represent an important risk for local or widespread outbreak of infectious diseases. Acute respiratory infections (ARIs) are the most common cause of hospital admission during hajj. Respiratory illness refers to influenzalike illness (ILI ) defined as the presence of fever and cough with and without other respiratory symptoms; nasal congestion, sore throat, sneezing or breathing problems. Protective behaviors such as using facemask, frequent usage of handrub, cough etiquette, social distancing and contact avoidance have been used to prevent its spread. Previous studies showed that hajj pilgrims that engaged in the recommended protective behaviors particularly hand hygiene and social distancing to have lower rate of